Trends and risk factors of stillbirths and neonatal deaths in Eastern Uganda (1982–2011): a cross‐sectional, population‐based study. Issue 1 (1st December 2016) - Kujala, Sanni; Waiswa, Peter; Kadobera, Daniel; Akuze, Joseph; Pariyo, George; Hanson, Claudia
Abstract: Objectives: To identify mortality trends and risk factors associated with stillbirths and neonatal deaths 1982–2011. Methods: Population‐based cross‐sectional study based on reported pregnancy history in Iganga‐Mayuge Health and Demographic Surveillance Site (HDSS) in Uganda. A pregnancy history survey was conducted among women aged 15–49 years living in the HDSS during May–July 2011 ( n = 10 540). Time trends were analysed with cubic splines and linear regression. Potential risk factors were examined with multilevel logistic regression with adjusted odds ratios (AOR) and 95% confidence intervals (CI). Results: 34 073 births from 1982 to 2011 were analysed. The annual rate of decrease was 0.9% for stillbirths and 1.8% for neonatal mortality. Stillbirths were associated with several risk factors: multiple births (AOR 2.57, CI 1.66–3.99), previous adverse outcome (AOR 6.16, CI 4.26–8.88) and grand multiparity among 35‐ to 49‐year‐olds (AOR 1.97, CI 1.32–2.89). Neonatal deaths were associated with multiple births (AOR 6.16, CI 4.80–7.92) and advanced maternal age linked with parity of 1–4 (AOR 2.34, CI 1.28–4.25) and grand multiparity (AOR 1.44, CI 1.09–1.90). Education, marital status and household wealth were not associated with the outcomes. Conclusions: The slow decline in mortality rates and easily identifiable risk factors calls for improving quality of care at birth and a rethinking of how to address obstetric risks, potentially a revival of the risk approach in antenatal care.